Analysis of the mismatch between school furniture and children - Gonçalves, Maria Antónia (2015)
The characteristics of school furniture are strongly associated with back and neck pain, referred by school-aged children. In Portugal, about 60% of the adolescents involved in a recent study reported having felt back pain at least once in the last three months. The aim of this study was to compare furniture sizes of the 2 types indicated for primary schools, within 9 schools, with the anthropometric characteristics of Portuguese students, in order to evaluate the mismatch between them. The sample consisted of 432 volunteer students. Regarding the methodology, 5 anthropometric measures were gathered, as well as 5 dimensions from the school furniture. For the evaluation of classroom furniture, a (mis)match criterion equation was defined. Results indicated that there is a significant mismatch between furniture dimensions and the anthropometric characteristics of the students.